Generating Digital Literacy Website: Upgrading the Understanding of Digital Literacy at SMA Yuppentek 1 Tangerang - Fithriana, Arin; Puspitasari, Anggun; Samsinar, Samsinar (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
This community service initiative introduces a website and Android-based application system to enhance digital literacy among educators at SMA Yuppentek 1, Tangerang. The prevailing issue pertains to the misuse of digital media, which significantly impacts societal well-being. Adolescents, being prolific users of digital platforms, face heightened vulnerability to various crimes stemming from their social media engagements. To address this, preventive measures necessitate an elevation of the partners' proficiency and comprehension in digital literacy. The initiative emphasizes social humanities and information systems, channeling efforts into fostering literacy and constructing website and Android applications to fortify the practice of digital literacy. The implementation strategy encompasses meticulous stages of preparation, execution, and reporting. The primary focus during the implementation phase centers on comprehensive solutions, comprising educating on digital literacy, providing insights into applications pertinent to digital literacy, crafting digital literacy applications, and formulating a digital literacy module. This program aims to foster a sustained understanding of digital literacy in youngsters, empowering educators to navigate and mitigate challenges posed by digital media misuse among adolescents. By equipping them with the requisite tools, it strives to fortify the capacity of educators in addressing the complexities inherent in adolescent digital engagement.